If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -0.75(8x + -12) + -9 = -2x Reorder the terms: -0.75(-12 + 8x) + -9 = -2x (-12 * -0.75 + 8x * -0.75) + -9 = -2x (9 + -6x) + -9 = -2x Reorder the terms: 9 + -9 + -6x = -2x Combine like terms: 9 + -9 = 0 0 + -6x = -2x -6x = -2x Solving -6x = -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -6x + 2x = -2x + 2x Combine like terms: -6x + 2x = -4x -4x = -2x + 2x Combine like terms: -2x + 2x = 0 -4x = 0 Divide each side by '-4'. x = 0 Simplifying x = 0
| (5k-10)-0-9= | | (4x+3)(3x-4)=0 | | yb+ax=c | | Y-2=(-2-3) | | 1.32(x+y)=32 | | Y-2=(-3-3) | | 12=6x-8x | | 284.7+14.6= | | -14.4=-0.6 | | 3(x*31)=31.3 | | 3s-6=5 | | -7k-9=1 | | 3x+-8y+4=11 | | 7x+4=-6x-22 | | 6(d+7)-20=6x | | 0.66+4=-0.33x-4 | | 3(10)=2y+6 | | 24+8k=9 | | 3(8)=2y+6 | | y(2-y)=6-(y(y)+3y-4) | | 3(4)=2y+6 | | 4y=-6x+8 | | (x+7)2-(x+(-2))(x+(-1))=0 | | 7x-11=5(x-2)+2x-1 | | x-2=-4y | | -6=k+1-8k | | 48x-37y= | | 3(0)=2y+6 | | 2+y=8+4 | | 3(-2)=2y+6 | | 8=-5x-3x | | y=-7+7 |